2022
DOI: 10.17507/tpls.1206.18
|View full text |Cite
|
Sign up to set email alerts
|

Developing Tasks to Foster Thai Students’ Willingness to Present in English

Abstract: It is evident that there are many factors that influence degrees of willingness to present among second language (L2) learners. Within the current context, less proficient students have shown clear signs of reluctance to deliver presentations in English language classrooms. Based on the researchers’ assumption and previous existing literature, there are two variables (i.e., topics for presentation and preparation time for presentation) central to the phenomenon situated. This article describes a pilot study wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Consequently, the application of Flip emerged as a valuable factor in enhancing overall speaking performance among learners. The results are in line with past studies conducted [7,13,18,19,21,[31][32][33]. This outcome reinforces the current concerns regarding the importance of previewing materials in the Flipped Classroom, emphasizing its role in enhancing learners' speaking performance [22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consequently, the application of Flip emerged as a valuable factor in enhancing overall speaking performance among learners. The results are in line with past studies conducted [7,13,18,19,21,[31][32][33]. This outcome reinforces the current concerns regarding the importance of previewing materials in the Flipped Classroom, emphasizing its role in enhancing learners' speaking performance [22].…”
Section: Discussionsupporting
confidence: 90%
“…In recent studies by Pratiwi et al (2022) and Sridhanyarat et al (2022), the effectiveness of the Flipped Classroom approach in enhancing speaking skills was explored [18,19]. Pratiwi et al's quantitative study focused on online speaking classes, revealing that the Flipped Classroom, coupled with in-class feedback, significantly improved learners' learning outcomes, emphasizing skills like content organization, coherence, grammatical accuracy, and pronunciation.…”
Section: Speaking Performance In the English Language Classroom And F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that aspects of task design other than the authenticity of topics and content affect L2 learners’ engagement. For example, a study of Thai university students’ willingness to present in English showed that presentation topic familiarity and preparation time reflected students’ willingness to present (Sridhanyarat et al, 2022). Some studies have also reported that the cognitive load of a task correlates with the degree of task completion because of growing anxiety (Chen & Chang, 2009; Donate, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%